Selenium Yeast Alleviates Escherichia coli-Induced Endometritis in Goats Under High Cortisol Background - Changning Yuan; Hanqing Li; Min Zhang; Zhihao Wang; Junsheng Dong; Luying Cui; Long Guo; Kangjun Liu; Jianji Li; Heng Wang (Animals)
During the postpartum period, domestic ruminants suffer elevated endogenous cortisol levels, which are associated with an increased risk of uterine infections. Selenium is a trace mineral nutrient with beneficial impacts on animals. The study aimed to investigate whether selenium yeast (SeY) could attenuate Escherichia coli (E. coli)-induced endometrial injury in goats with high cortisol background. Goats were examined after oral SeY administration for 21 days and were treated with glacial acetic acid, E. coli, and hydrocortisone to establish an endometritis model with high cortisol background. The results showed that endometrial injury caused by E. coli was aggravated under high cortisol background. Supplementation with SeY alleviated endometrial inflammation and serum LDH content. The mRNA expression of pro-inflammatory cytokines and defensin beta 2 and the phosphorylation level of the mitogen-activated protein kinase (MAPK) and nuclear factor kappa-b (NF-κB) signaling pathways were decreased by SeY supplementation. Total antioxidant capacity and antioxidant enzymes activities were increased by SeY supplementation, but malondialdehyde and 4-hydroxynonenal content were decreased. Moreover, nuclear factor erythroid-2 related factor 2 (NRF2) in the nucleus, heme oxygenase-1, and NAD(P)H quinone dehydrogenase 1 were increased by SeY supplementation. So, supplementation with SeY alleviated E. coli-induced endometritis in goats by activating the NRF2 pathway and inhibiting the activation of the MAPK and NF-κB pathways under postpartum stress.